Psychosocial and physical stressors among healthcare providers in Intensive Care Unit and the Emergency and Trauma Department / Siti Khuzaimah Ahmad Sharoni ... [et al.] - Ahmad Sharoni, Siti Khuzaimah; Jamal, Khairul Naim; Fauzi, Rosuzeita; Mohd Yusoff, Mohd Khairizam (2021)
Healthcare providers often reported having physical and mental stress. It may be due to stress-related health problems that contribute to a severe public health issue. This study aims to determine the psychosocial and physical stressors among healthcare providers in the Intensive Care Unit and the Emergency and Trauma Department of Hospital Sultanah Bahiyah, Alor Setar, Kedah. A descriptive cross- sectional study with a purposive sampling technique was conducted between July and August 2020. The Job Content Questionnaire was used as the measurement tool, and the data were analysed with descriptive and inferential statistics. A total of 140 nurses and medical assistants participated in the study. The findings show that although the respondents have good working condition, they experienced high physical stressors. The results indicated that the job control differed statistically and significantly for gender, job category, working area and working hours. It also revealed a significant difference between psychological job demand and working hours. Physical demand is associated with gender, marital status, job category, age and working hours. Lastly, the results indicated a statistically significant association between social support with gender and working area. It can be concluded that the male gender, specifically those working in ETD, have better working conditions. However, most of them, especially the younger medical assistants, male and single ones, reported experiencing physical demand. Healthcare providers who have long working hours (per week) also have high physical and psychological job demands. Therefore, special attention should be given to this group of healthcare providers to prevent them from suffering any physical and psychological harm and injury.